Hair cortisol concentration and glycated hemoglobin in African American adults. (October 2016) - Lehrer, H. Matthew; Dubois, Susan K.; Maslowsky, Julie; Laudenslager, Mark L.; Steinhardt, Mary A.
Highlights: First study examining hair cortisol/hair DHEA and glycemic control in African Americans. HbA1c increased with hair cortisol concentrations; stronger relationship in those with HbA1c > 6.5%. Hair DHEA was not related to HbA1c . Abstract: Background: African Americans have higher diabetes prevalence compared to Whites. They also have elevated cortisol levels − indicating possible HPA axis dysregulation − which may raise blood glucose as part of the biological response to physiological and psychosocial stress. Little is known about chronic cortisol levels in African Americans, and even less about the role of chronically elevated cortisol in type 2 diabetes development in this racial group. Purpose: We used analysis of cortisol in hair to examine associations of long-term (∼3 months) cortisol levels with glycated hemoglobin (HbA1c ) in a group of African American adults. In exploratory analyses, we also studied the relationship of hair dehydroepiandrosterone (DHEA) with HbA1c . Method: Participants were 61 community-dwelling African American adults (85% female; mean age 54.30 years). The first 3 cm of scalp-near hair were analyzed for cortisol and DHEA concentration using enzyme-linked immunoassay analysis. Glycated hemoglobin was assessed, and regression analyses predicting HbA1c from hair cortisol and DHEA were performed in the full sample and in a subsample of participants (n = 20) meeting the National Institute of Diabetes and Digestive Kidney Disease (NIDDK) criteria for type 2 diabetes (HbA1c ≥ 6.5%). Results: In the full sample, HbA1c increased with hair cortisol level (β = 0.22, p = 0.04, f 2 = 0.10), independent of age, sex, chronic health conditions, diabetes medication use, exercise, and depressive symptoms. In the subsample of participants with an HbA1c ≥ 6.5%, hair cortisol was also positively related to HbA1c (β = 0.45, p = 0.04, f 2 = 0.32), independent of diabetes medication use. Glycated hemoglobin was unrelated to hair DHEA in both the full sample and HbA1c ≥ 6.5% subsample. Conclusion: Long-term HPA axis dysregulation in the form of elevated hair cortisol is associated with elevated HbA1c in African American adults.